1999
DOI: 10.1038/sj.cr.7290021
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirus-mediated herpes simplex virus thymidine kinase gene therapy approach for hepatocellular carcinoma

Abstract: The therapeutic effect of herpes simplex virus thymidine kinase/ganciclovir (HSV-tk/GCV) system on hepatocellular carcinoma was studied in this experiment. The tk-containing retroviral recombinants were used to infect hepatoma cells (BEL-7402) and the cells were treated with ganciclovir (0-1000 μg/ ml). The results showed that HSV-tk gene could be efficiently transferred in vitro into hepatoma cells and stably expressed. The growth potential of the tk-containing cells was significantly inhibited by GCV (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The above results indicated that the construction strategy of the recombinant vector was correctly performed and the retrovirus containing hHO-1 could be stably and efficiently expressed in transfected-VSMC. In fact, several other transgenic cell lines for expression of the specific target genes had been established in this lab by using retroviral [11], [20].…”
Section: Increase Of Cellular Cgmp and Decrease Of Mapk Phosphorylationmentioning
confidence: 99%
“…The above results indicated that the construction strategy of the recombinant vector was correctly performed and the retrovirus containing hHO-1 could be stably and efficiently expressed in transfected-VSMC. In fact, several other transgenic cell lines for expression of the specific target genes had been established in this lab by using retroviral [11], [20].…”
Section: Increase Of Cellular Cgmp and Decrease Of Mapk Phosphorylationmentioning
confidence: 99%
“…Ad.TK can be safely used in HCC patient upto 2X10 12 viral Particles/patient [35]. The HSV-TK gene has been successfully transferred into hepatoma cells (BEL-7402), and the growth potential of these cells was significantly inhibited by the application of GCV [36]. The bystander effect was further boosted by a combination therapy of co-expression of TK and E-cadherin genes in adenoviral vector.…”
Section: Variations Of Original Hsv-tk Approachmentioning
confidence: 93%
“…The difficulty of employing these modalities as a treatment for HCC is the ability to design a vector that would be specific for HCC and not the surrounding benign tissue [20]. Several viral vectors, including retroviral, lentiviral, adeno-associated viral (AAV), herpes viral, and adenoviral variations, are currently available for gene therapy and are being explored for HCC gene therapy [21][22][23]. In addition, Iwasaki et al have recently described the use of nanoparticles as a means of gene delivery.…”
Section: Gene Therapymentioning
confidence: 99%